ANALISIS KARAKTERISTIK INDIVIDU, BEBAN KERJA, KONFLIK TERHADAP STRES DALAM MENINGKATKAN KINERJA - Legawa Tegar Ramadhan (Prodi Magister Manajemen FE-UST, 2021)
This study conducted to examine individual characteristics variables, workload, stress conflict in improving the performance of health workers and non-health workers PUKSESMAS Depok II, Sleman, D.I. Yogyakarta. The sampling technique used a census. The sample is health workers and non-health workers. The analysis technique used path analysis with the SPSS 18.0 and SmartPLS 3.2.8. Based on the results of data analysis and the hypothesis testing are concluded that the individual characteristic variables have a positive and insignificant effect on stress variables and have a significant positive effect on performance variables. Workload variables have a positive and insignificant effect on stress variables and have a positive but not significant effect on performance variables. Conflict variables have a significant positive effect on performance variables and have a significant negative effect on performance. And Stress Variables have a significant positive effect on performance. Keywords: Individual Characteristics, Workload, Conflict, Stress, Performance.